Migrations to Southern Patagonia: Reconstructing the Trajectories of Galician Families (1902-1940) - Allende, Pablo Julián (Madrygal. Revista de Estudios Gallegos, 2024)
This article analyzes how social networks and family history shaped migration to Southern Patagonia, Argentina, between 1902 and 1940. Drawing on a comparative reconstruction of three trajectories of Galician families, it examines the mechanisms of mobility, settlement, and rootedness in Puerto Deseado, Puerto San Julián, and Ushuaia, in connection with the Atlantic nodes of departure and transit (Vigo and Santos). The temporal scope corresponds to the full cycle of the trajectories under study, from the initial arrival (1902) to definitive settlement (ca. 1940). The study offers an account of regional migratory processes and their articulation with transnational circuits, contributing to a more precise understanding of the demographic and social dynamics of Southern Patagonia in the first half of the 20th century.
Keywords: Galician Migration; Argentine Patagonia; Twentieth Century; Family Trajectories